Description of U6719‐004 wheat germplasm with YrAS2388R stripe rust resistance introgression from Aegilops tauschii. Issue 1 (27th October 2022) - Lopez, Selena R.; Wiersma, Andrew T.; Strauss, Nikayla M.; Watkins, Tara; Baik, Byung‐Kee; Zhang, Guorong; Sehgal, Sunish K.; Kolb, Frederic L.; Poland, Jesse A.; Mason, R. Esten; Carter, Arron H.; Olson, Eric L.
Abstract: In recent years, stripe rust has become an increasingly problematic disease affecting wheat ( Triticum aestivum L.). Although stripe rust resistance genes Yr28 and YrAS2388R have been successfully transferred from Aegilops tauschii Coss. to hexaploid wheat, these genes have not been widely used for stripe rust resistance breeding largely due to a lack of publicly available and well‐adapted germplasm. Here we describe U6719‐004 (Entry 538 of D‐genome nested association mapping population, Reg. No. MP‐14, NSL 536301 MAP), a hexaploid wheat germplasm carrying YrAS2388R stripe rust resistance derived from Ae. tauschii accession TA1718 that is well adapted to U.S. wheat production environments. U6719‐004 (KS05HW14‐3/3/KS05HW14‐3/TA1718//KS05HW14‐3) was developed using a combination of direct hybridization of TA1718 with the hard white winter wheat line KS05HW14‐3 followed by two rounds of backcrossing and three generations of single seed descent. U6719‐004 stripe rust resistance was characterized under controlled and natural conditions. Using gene‐based markers, TA1718 and U6719‐004 were confirmed to be YrAS2388R carriers. Grain yield for U6719‐004 was evaluated in 11 year‐by‐location environments across the United States. Grain quality parameters were measured in four year‐by‐location environments. Compared with the recurrent wheat parent KS05HW14‐3 and locally adapted check cultivars, the Ae. tauschii introgression had little to no impact on U6719‐004 grain yield or quality. The availability of U6719‐004 will enable the use of YrAS2388R for stripe rust resistance breeding efforts. Core Ideas: The hexaploid wheat germplasm U6719‐004 carries stripe rust resistance gene YrAS2388R . U6719‐004 is broadly adapted to wheat production environments of the United States. U6719‐004 has acceptable grain yield and grain quality.